Legal Reform in Preventing Cyber Radicalism by Optimizing the Role of Social Media as a Means of Building National Defense Awareness among the Younger Generation - Maulana Al Qurthubi; Albertus Wahyurudhanto; Kif Aminanto (Indonesian Journal Publisher, 2026)
This study aims to examine the legal challenges in preventing cyber radicalism through social media among the younger generation and to propose legal reforms by optimizing social media as a tool to strengthen national defense awareness in the digital era. The development of information technology has shifted the pattern of radicalism from conventional forms to digital radicalism, which utilizes social media as a medium for spreading extreme ideological propaganda quickly, anonymously, and across national borders. This condition has led to various legal issues, including weak normative regulation of digital radicalism, limited penal approaches, inadequate supervision of social media platforms, and low levels of digital literacy and legal awareness among the younger generation. This study employs a normative juridical research method using both a statutory and conceptual approach, analyzing the 1945 Constitution of the Republic of Indonesia, the Electronic Information and Transactions Law, the Law on the Eradication of Criminal Acts of Terrorism, and relevant regulations on national defense and cybersecurity. The results indicate that policies to combat cyber radicalism in Indonesia are still repressive and have not been able to accommodate the development of digital ideological threats in a preventive and participatory manner. Therefore, legal reform is needed through strengthening social media regulations, developing an integrated digital monitoring system, integrating national defense education and digital literacy, and developing a digital counter-narrative based on Pancasila values ​​to shape a younger generation with national defense awareness and ideological resilience in the digital age.